Virulence and resistance determinants of Klebsiella pneumoniae isolated from a Portuguese tertiary university hospital centre over a 31-year period - Caneiras, Catia (2019)
© 2018 Elsevier España, S.L.U. and Sociedad Española de Enfermedades Infecciosas y Microbiología Clínica. All rights reserved.